A case of T4 toxicosis complicated by thyroid storm with an unusual precipitant - Oluwaseyitan Andrew Adesegun; Akolade O. Idowu; Bamikole Osibowale; Theophilus Ajiro; Daniel Ezuduemoih; Ayokunle Osonuga (Babol University of Medical Sciences, 2020)
Background: Thyrotoxicosis, though commonly encountered in endocrinology practice in Nigeria, seldom presents solely as thyroxine (T4) toxicosis. Thyroid storm, a known life-threatening complication of thyrotoxicosis, can be precipitated by myriad factors. Fine need aspiration for cytology is not known, and has not been previously reported (to the best of our knowledge) to precipitate thyroid storm. Case Presentation: The case described is that of a 55 year old woman who presented with a neck swelling and features of hyperthyroidism, with biochemical parameters in keeping with T4 toxicosis. Investigating the patient necessitated a fine needle aspiration of the thyroid swelling. The patient thereafter developed hyper-metabolic features, and subsequently progressed to confusion and loss of consciousness few hours following the procedure. Close monitoring and medical management with anti-thyroid and other supportive therapies, resulted in an improved clinical condition. Conclusion: T4 toxicosis is a distinct biochemical entity of clinical significance. Physicians should bear in mind that micro-trauma from an investigation such as fine needle aspiration of the thyroid gland can tilt a thyrotoxic patient into thyroid storm, and this risk should be considered and prepared for by physicians and patients.